KEEFEKTIFAN PENGGUNAAN TEKNIK THINK PAIR SHARE (TPS) DALAM KETERAMPILAN MEMBACA MEMAHAMI BAHASA JERMAN SISWA KELAS X SMA NEGERI 1 KAB. BARRU - Tahir, Resky Amalia; Rijal, Syamsu; Fatimah, Syarifah (Universitas Negeri Makassar, 2020)
Abstract. This research was conducted to obtain data and information about reading skills to understand German students. This research is Quasi Experimental Design. The research population is all students grade X SMA Negeri 1 Kab. Barru consisted of 12 classes totaling 396 students. Sampling in this study uses random sampling with a sample consisting of 2 classes, namely class X IPS 6 as an experimental class with 27 students and class X IPS 4 as a control class with the same number of students, 27 people. The research data was obtained through reading skills tests understanding German. Data were analyzed using t-test with the results showing that t-count 11.89> t-table 2.007 with a significance level of 0.05. Thus this study shows that the use of Think Pair Share techniques is effective in improving reading skills in understanding German students' language.